Pengaruh Ulasan Konsumen dan Nilai Pelanggan serta Celebrity Endorser Terhadap Keputusan Pembelian pada Ecommerce Shopee di Samarinda - Salim, Peter Wijaya; Wasil, Muhammad (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2025)
This study aims to analyze the influence of consumer reviews, customer value, and celebrity endorsers on purchasing decisions on the Shopee e-commerce platform in Samarinda. The research used a quantitative approach with a descriptive method. The sampling technique used purposive sampling with a total of 80 Shopee users in Samarinda who met the research criteria. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using SPSS version 25 through validity tests, reliability tests, multiple linear regression analysis, correlation coefficient tests, coefficient of determination tests, F-tests, and t-tests. The results showed that consumer reviews and customer value had a positive and significant effect on purchasing decisions. Meanwhile, celebrity endorsers did not have a significant effect on purchasing decisions. Simultaneously, consumer reviews, customer value, and celebrity endorsers influenced purchasing decisions. This study indicates that consumers tend to prioritize user reviews and perceived value over public figure influence in making purchasing decisions on e-commerce platforms. This research is expected to serve as a reference for companies in developing more effective digital marketing strategies to improve consumer purchasing decisions.